The study of methods and tools for production of multi-parameter reference materials for composition and properties of coatings - V. V. Kazantsev; A. S. Vasiliev (Стандартные образцы)
The article presents tests results of reference materials of composition and properties of coatings. RMs with nickel coating on steel and permalloy coating on silicium are used. Multiparameter RMs are developed.